Retroperitoneal Ectopic Location of an Intrauterine Device Revealed by Renal Colic: An Exceptional Case - Idriss Ziani; Imad Boualaoui; Ahmed Ibrahimi; Hachem El Sayegh; Lounis Benslimane; Yassine Nouini (Case Reports in Urology)
The intrauterine device (IUD) is one of the most effective contraceptive methods. Its Pearl Index is less than 1 per 100 women. It is the most used method around the world: about 100 million users. However, its insertion can cause certain complications, such as infection, expulsion, or perforation essentially when the rules of use are poorly applied. Perforation remains exceptional but one of the most serious complications. Indeed, after a perforation, the IUD could be located in different neighboring organs. We report a new case of IUD ectopic location in the peritoneal cavity, which was diagnosed 7 years after the insertion and as part of the renal colic assessment. The surgery was performed to remove the IUD which was embedded in the peritoneum and compresses the ureter and causes dilation upstream. To our knowledge, this is the first case reported in the literature of an ectopic location in the retroperitoneal space of an intrauterine device.